Sufism as Psychotherapy to Overcoming Relapse in Schizophrenic Patients - Husna, Mai Tiza; Saputri, Meza (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2024)
Abstract: Sufism as psychotherapy provides treatment based on Islamic teachings that is intended for every human being who experiences mental illness. Mental illness referred to as severe mental disorder (psychosis), one of which is schizophrenia, which sufferers tend to experience relapse (recurrence). The purpose of this study is to find out how the use of Sufism as psychotherapy in dealing with relapse of people with schizophrenia and to prove empirical facts that Sufism can be used as a psychotherapy for people with schizophrenia based on previous studies. This research method uses literature review, literature searches are carried out through Google Scholar. Search results from Google Scholar found 12 journals, and 7 journals were eliminated, then 5 journals were accepted and analyzed. The results showed that Sufism as a psychotherapy could be a form of treatment for people with schizophrenia. The forms of Sufism as psychotherapy are Qur'anic healing therapy, Sufi healing therapy and spiritual neuroscience, as well as collaboration of Sufistic psychotherapy with traditional suwuk bobok Jowo, then audio therapy of the Qur'an, ablution therapy, prayer, and remembrance. Sufism as psychotherapy can make the heart (qalb) and soul calm, serene, and peaceful. So that the symptoms of schizophrenics such as anxiety, hallucinations, and delusions can be reduced. Keywords: Sufism; Psychotherapy; Relapse; Schizophrenic patients